Fukomys anselli (Rodentia: Bathyergidae). (1st December 2021) - Begall, Sabine; Burda, Hynek; Caspar, Kai R
Abstract: Fukomys anselli (Burda, Zima, Scharff, Macholán, and Kawalika 1999) is a bathyergid commonly known as Ansell's mole-rat. This tooth-digging subterranean rodent lives in cooperatively breeding family groups. It is a small-bodied representative of the genus Fukomys, whose members are distributed in sub-Saharan Africa. Fukomys anselli is endemic to central Zambia and occurs in mesic woodland and agricultural areas. In rural settings, F. anselli is frequently hunted for consumption, but it is unclear whether this significantly impacts its population integrity. Fukomys anselli is listed as "Least Concern" (LC) with a declining population trend by the International Union for Conservation of Nature Red List of Threatened Species.